Persepsi Remaja terhadap Penyuluhan Kesehatan Reproduksi Remaja di Kecamatan Wirobrajan Yogyakarta - Nur Budyantara; Jemadi Jemadi (Jurnal Maksipreneur, 2011)
The research on adolescence perception to their reproduction health guidance in Wirobrajan District, Yogyakarta could give an illustration on a very well, well or poor perception guidance variables. Adolescence reproduction health guiding function was to guide and to direct adolescence in order to avoid from a disadvantageous behaviour for their future lives such as free association, pre-marriage sexual intercourse, sexual affected disease, drugs abuse, drinking, criminal acts and soon. Adolescence reproduction health program was conducted through several approaches were among others: Firstly, family communication approach i.e. a program given through interpersonal communication between parents and their adolescence phase and learning/ teaching approach, aimed to give adolescence reproduction health program in school through intra-curricular and extra-curricular. Secondly, a counselling approach meant that given to the adolescence and their parents in a school guidance activity form as well as society through social group/ organization such as youth workshop, Family Wellness Program (PKK), BKR, and soon. From the research result, it was known that adolescence perception to reproduction health guidance was averagely good, except its perception credibility was very good, adolescence concept or ways most liked on adolescence health guidance was conducted a direct guidance using demonstration tools. Viewed from an adolescence perception difference on adolescence reproduction health guidance was based on sex, age, origin, school, parent educational level and occupation. From the analysis result, there was no respondent perception difference viewed from sex, age, origin, school, parent educational level and occupation.